2016
DOI: 10.7705/biomedica.v36i2.2693
|View full text |Cite
|
Sign up to set email alerts
|

Medication errors in outpatient care in Colombia, 2005-2013

Abstract: anti-infective drugs for systemic use (OR=1.99, CI 95%: 1.574-2.525, p<0.001), confusion generated with the name of the drug (OR=1.28, CI 95%: 1.051-1.560, p=0.014), and trouble interpreting prescriptions (OR=1.32, CI 95%: 1.037-1.702, p=0.025) increased the risk for error reaching the patient. Conclusions: It is necessary to develop surveillance systems for medication errors in ambulatory care, focusing on the prescription, transcription and dispensation processes. Special strategies are needed for the preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 18 publications
1
10
0
6
Order By: Relevance
“…The findings of reports on drugs omission, inadequate storage conditions and wrong medication can be the reflection of the lack of a drug distribution system, whose purpose, precisely, is to reduce these errors [27]. These results are consistent with a study conducted in the hospitalization service of a clinic in the city of Cali (Colombia) [28] and another study conducted by Machado et al for 8 years in ambulatory pharmacies in different cities of Colombia [26]. However, it is necessary to emphasize that the comparison of these results with other studies is difficult because of the use of different types of classification and several settings of study (community, hospital, ambulatory, etc.).…”
Section: Drugs Involved In the Reportssupporting
confidence: 83%
See 1 more Smart Citation
“…The findings of reports on drugs omission, inadequate storage conditions and wrong medication can be the reflection of the lack of a drug distribution system, whose purpose, precisely, is to reduce these errors [27]. These results are consistent with a study conducted in the hospitalization service of a clinic in the city of Cali (Colombia) [28] and another study conducted by Machado et al for 8 years in ambulatory pharmacies in different cities of Colombia [26]. However, it is necessary to emphasize that the comparison of these results with other studies is difficult because of the use of different types of classification and several settings of study (community, hospital, ambulatory, etc.).…”
Section: Drugs Involved In the Reportssupporting
confidence: 83%
“…Given that the interest of this work corresponds to drugs, it can be mention that the frequency of reports related to this supply is within the numbers identified in studies such as ENEAS with 37.4% [10], IBEAS with 8,23% [16] and SYREC with 24.6% [23]. In relation to Colombian studies, some studies covering several years, and more than 5 million people have been published [24][25][26], but it was not possible to contrast the results, since it is used another approach and a different classification to the one used by international studies.…”
Section: Drugs Involved In the Reportsmentioning
confidence: 99%
“…Among these, 351 articles were excluded after title screening and the abstract of the 784 remaining papers was assessed. Finally, 461 publications were excluded following the eligibility criteria and thus, 323 articles that had interpretable data and fulfilled the eligibility criteria were used for data extraction…”
Section: Resultsmentioning
confidence: 99%
“…In Colombia, a study of medication errors using outpatient pharmacy services and national medication dispensing from January 2005 to September 2013 found a total of 14 873 medication errors where ~16% reached the patient and 0.7% caused harm. Those errors occurred mainly in the administration, dispensing, transcription, and interpretation of prescriptions 107 . In Mexico, a study determining the frequency of potential drug‐drug and drug‐disease interactions among 624 ambulatory patients over 50 years of age with nonmalignant pain syndrome, showed that patients received was an average of 5.9 ± 2.5 prescribed medicines.…”
Section: Introductionmentioning
confidence: 99%